Heat insulating sheet and its manufacturing method
Patent Information
- Application Number
- JP2023055241
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-03-30
AI Technical Summary
【0012】 本発明によれば、熱膨張による圧縮応力で損壊しない圧縮強さと優れた断熱性とを兼ね備えているうえ、施工に際して機器の曲面に沿って曲げても破損しにくいので極めて効率よく施工することが可能な断熱シートを提供することができる。
Smart Images

Figure 0007629953000003 
Figure 0007629953000004 
Figure 0007629953000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat insulating sheet and a method for manufacturing the heat insulating sheet, and more particularly to a flexible heat insulating sheet that can be applied to a curved surface and a method for manufacturing the heat insulating sheet. [Background technology]
[0002] Insulation materials are used for various purposes, such as lining the steel shell of a cylindrical bottomed vessel that temporarily holds molten metal, insulating the furnace body of a small heating furnace, and keeping large-diameter pipes through which high-temperature fluid flows warm. For example, when insulating materials are applied to the furnace body of a heating furnace, insulation materials made of low thermal conductivity materials mainly composed of inorganic fine particles such as silica are used for the purpose of significantly suppressing heat radiation from the furnace body and reducing the thermal load on the steel shell that constitutes the furnace body. Low thermal conductivity materials generally have a thermal conductivity of 0.08 W / (m·K) or less at 800°C, and the maximum operating temperature is about 1000°C, and there are also insulation products for high temperatures with a maximum operating temperature of about 1200°C. In addition, insulation materials made of low thermal conductivity materials are often used in thicknesses of 3 to 5 mm.
[0003] However, since low thermal conductivity materials are very fragile, when insulating materials are applied to equipment and piping having curved surfaces such as the above-mentioned molten metal container and large-diameter piping, insulating materials having a thickness of 3 to 5 mm may break when bent along such curved surfaces. For this reason, when applying insulating material 2 made of a low thermal conductivity material to the inner wall surface of a cylindrical molten metal container 1 with a bottom, for example, it was necessary to apply a plurality of rectangular insulating materials in a polygonal shape to match the curved surface of the molten metal container 1, as shown in FIG. 1. In particular, in the case of a part including a curved surface with a small radius of curvature such as a mixed-rail car or a small-diameter container, it is necessary to use a large number of rectangular insulating materials having small areas, which takes time and effort to apply, and there is a risk of the insulating properties being reduced due to the increase in the number of joints. When applying insulating material to the inner surface side of the molten metal container, a fireproof material may be further applied inside the insulating material as necessary.
[0004] Therefore, various types of heat insulating materials have been proposed that are designed to be applied along curved surfaces. For example, Non-Patent Documents 1 and 2 disclose a technique for manufacturing heat insulating materials in various forms such as a futon-like, quilt-like, segmented, etc., by storing a low thermal conductivity material made of nano-sized silica particles (fumed silica) in a bag and then sewing it. In addition, Patent Document 1 proposes a composite heat insulating material in which a reinforcing material made of inorganic or organic fibers and having a tensile strength of 60 N / 25 cm or more is bonded to at least one side of a molded body made of a low thermal conductivity material, and Patent Document 2 proposes a heat insulating fabric in which fumed silica powder is contained in a textile fabric layer. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Catalog "High-performance Insulation Material Microtherm", Japan Microtherm Co., Ltd., February 2004, page 5 [Non-Patent Document 2] Catalog "Porextherm WDS", Kurosaki Harima Corporation, October 1, 2005, page 5 [Patent documents]
[0006] [Patent Document 1] JP 2016-205728 A [Patent Document 2] Special Publication No. 2022-508727 Summary of the Invention [Problem to be solved by the invention]
[0007] Although the insulating materials described in Non-Patent Document 1 and Non-Patent Document 2 above can be used for construction along curved surfaces, the insulating material placed in a bag and sewn cannot avoid the occurrence of so-called heat leakage, which results in localized insufficient insulation, because the low thermal conductivity material is interrupted or thinned at the seams during construction as well as at the sewn parts. In addition, low thermal conductivity materials mainly made of nano-sized particles have relatively low strength, so there have been problems with them being damaged inside the bag during handling, or damaged by ferrostatic pressure or compressive stress due to thermal expansion of the refractory material after construction.
[0008] The composite insulation material of Patent Document 1 is considered to be able to combine compressive strength that is not broken by compressive stress due to thermal expansion and excellent thermal insulation, but there is a limit of a maximum curvature radius of 1500 mm. In the insulating fabric of Patent Document 2, glass fiber is used as the main material of the textile fabric in all of Examples 1 to 4, so it is considered that the glass transition temperature must be taken into consideration for the heat resistance temperature. The present invention has been made in consideration of the above circumstances, and aims to provide an insulating sheet that has excellent workability, in addition to having compressive strength that is not broken by compressive stress due to thermal expansion and excellent thermal insulation, and is unlikely to break even when bent along the curved surface of equipment during installation. [Means for solving the problem]
[0009] In order to achieve the above-mentioned object, the inventors conducted extensive research and discovered that when a molded body of a low thermal conductivity material obtained by blending an organic resin with inorganic fine particles such as silica as the main material is heated and compressed, the organic resin melts and heat-fuses to the inorganic fine particles, thereby functioning as a binder, thereby increasing the amount of deflection when the insulation sheet is bent, thereby completing the present invention.
[0010] That is, the heat insulating sheet according to the present invention is a molded body in which inorganic fine particles made of a metal oxide as a main material are mixed with an organic resin at a content in the range of 3 to 40 mass %, the organic resin is bonded to the inorganic fine particles by thermal fusion, When measuring the bending strength of a 5 mm thick object with a span of 100 mm, the deflection at break is 3.0 mm or more. 10mm or lessand the thermal conductivity at 600℃ is 0.03W / (m·K) or more 0.05W / (m K) or less The compressive strength is 0.55MPa or more and 1.56MPa or less, and the bulk density is 200-500kg / m 3 in It is characterized by the fact that
[0011] In addition, the method for producing a heat insulating sheet according to the present invention includes mixing inorganic fine particles made of a metal oxide as a main material with an organic resin, compressing the mixture, and then heat-compressing and molding the resulting molded product. (Except when curing in a pressurized water vapor saturated atmosphere) In this manner, the organic resin is thermally fused to the inorganic fine particles. Effect of the Invention
[0012] According to the present invention, it is possible to provide an insulating sheet that combines compressive strength that does not break due to compressive stress caused by thermal expansion with excellent insulating properties, and is also resistant to damage even when bent along the curved surface of equipment during installation, making it possible to provide an insulating sheet that can be installed extremely efficiently. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a perspective view showing a conventional insulating material applied to the inner wall surface of a molten metal container. [Diagram 2] 1 is a perspective view showing a state in which an insulating sheet according to an embodiment of the present invention is applied to an inner wall surface of a molten metal container. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the heat insulating sheet according to the present invention will be described. The heat insulating sheet according to the embodiment of the present invention has a form of a molded body in which inorganic fine particles of inorganic oxide as a main material are mixed with organic resin, and this molded body further contains fireproof fiber and infrared scattering material as necessary. In addition, the heat insulating sheet according to the embodiment of the present invention can be molded to a thickness of about 3 to 5 mm required for application as a heat insulating material for small containers, and the deflection amount at break when a 5 mm thick sheet is measured for bending strength with a span of 100 mm is 3.0 mm or more. Therefore, with the heat insulating sheet according to the embodiment of the present invention, even if a 5 mm thick sheet is bent along a curved surface with a curvature radius of 500 mm, it can be applied without breaking. The bending deflection amount can be changed by adjusting the type, form, and amount of the organic resin to be blended, the heating temperature and holding time during heat compression molding. In addition, the upper limit of the above deflection amount is about 10 mm, and in this case, even if a 5 mm thick heat insulating sheet is bent along a curved surface with a curvature radius of 125 mm, it can be applied without breaking.
[0015] Depending on the manufacturing method, the insulating sheet of the embodiment of the present invention can be manufactured into a sheet shape that is generally 600 mm or more wide. As a result, as shown in Figure 2, the insulating sheet 12 of the embodiment of the present invention can be applied in a rolled up state to the inner wall surface of a cylindrical molten metal container 11 with a bottom, which not only improves workability but also minimizes the number of seams during application, thereby preventing the problem of heat leakage.
[0016] In addition, by using alumina instead of or in addition to silica in the inorganic fine particles in the heat insulating sheet of this embodiment of the present invention, the heat resistance temperature can be increased to about 1200°C, allowing it to be used for a long period of time at the normal usage temperature of 1000°C. Also, since the thermal conductivity of the heat insulating sheet of this embodiment of the present invention at 600°C can be made 0.05 W / (m K) or less, the amount of heat dissipation can be kept low, thereby achieving the effect of reducing thermal energy consumption.
[0017] Next, each material contained in the heat insulating sheet will be specifically described. The inorganic fine particles are made of a metal oxide having a heat resistance at a high temperature of about 1000 to 1200°C. The metal oxide is preferably one or more selected from the group consisting of silica, alumina, magnesia, mullite, and zirconia. The inorganic fine particles preferably have an average particle size of 0.5 μm or less. This can reduce the void size in the heat insulating sheet, and in particular, when the heat insulating sheet contains refractory fibers or infrared scattering materials, the void size between these and the inorganic fine particles can be reduced, so that the convection heat transfer of gas at high temperatures can be suppressed. In this specification, the average particle size is the 50% diameter (D50) based on volume measured by a laser diffraction type particle size distribution measuring device.
[0018] The refractory fiber is a fiber made of an inorganic composition having a heat resistance of about 600 to 1600°C. Representative refractory fibers include, but are not limited to, glass fibers, alumina fibers, mullite fibers, CaO·6Al 2 O 3 Examples of the refractory fiber include calcia aluminate fibers, zirconia fibers, biosoluble fibers, and AES (alkaline earth silicate) fibers, and it is preferable to use one or more fibers selected from the group consisting of these fibers. The average fiber diameter of this refractory fiber is preferably 1 μm to 13 μm, and more preferably 2 μm to 10 μm. In this specification, the average fiber diameter is obtained by photographing the fiber group to be measured with an electron microscope, measuring the width direction distance of 200 or more fibers selected arbitrarily from the obtained image, and calculating the arithmetic average of these.
[0019] The fire-resistant fiber may contain non-fiber particles of the same material. In this case, the content of the non-fiber particles is preferably 60 parts by mass or less, more preferably 50 parts by mass or less, based on 100 parts by mass of the fire-resistant fiber. In particular, the content of the non-fiber particles having an average particle size of 425 μm or more is preferably 3 parts by mass or less, more preferably 1 part by mass or less.
[0020] The infrared scattering material is not particularly limited as long as it has a heat resistance of 800°C or more and is made of a composition capable of reducing heat transfer by radiation, but infrared reflectivity is preferable. Examples of such compositions include silicon carbide, titanium dioxide, iron, zirconium silicate, zirconia, etc., and it is preferable to use one or more selected from the group consisting of these compositions. In addition, the above-mentioned infrared scattering material preferably has an average particle size of 0.1 μm to 3.0 μm, and in particular, the upper limit is more preferably 2.0 μm or less, which is the average particle size equivalent to the peak wavelength at 1200°C of infrared rays that cause radiative heat transfer.
[0021] The organic resin is preferably one that melts at 150°C or less. Examples of such organic resins include, but are not limited to, polyester, polyvinyl alcohol, polyethylene, polypropylene, or a composite of two or more of them. In the case of a composite, a core-sheath fiber of polyethylene (PE) / polypropylene (PP) is preferable. The organic resin may be in the form of particles or fibers. In particular, in the case of a core-sheath fiber such as PE / PP, the core part remains even after melting, so it is more preferable in terms of maintaining excellent bending performance. The above-mentioned core-sheath fiber is a fiber having a double structure of a core part made of polypropylene and a sheath part made of polyethylene that surrounds the core part in a substantially concentric axial shape. In the case of a particulate form, an average particle size of 0.5 mm or less is preferable in terms of ensuring good dispersibility. On the other hand, in the case of a fibrous material, the fiber thickness scale T (dtex), calculated by substituting the measured length L (m) and weight W (g) into T = (10,000 × W) / L, is preferably in the range of 1.0 to 20, and the fiber length measured by an electron microscope is preferably in the range of 3 to 20 mm.
[0022] When the organic resin is in the form of particles, the amount of deflection when the heat insulating sheet is bent can be changed by adjusting the average particle size, particle size distribution, heating temperature and holding time during heat compression molding. On the other hand, when the organic resin is in the form of fibers, the amount of deflection when the heat insulating sheet is bent can be changed by adjusting the fiber diameter, fiber length, heating temperature and holding time during heat compression molding. The content of the organic resin in the heat insulating sheet is preferably 3 to 40 mass%, more preferably 5 to 20 mass%. If this content is less than 3 mass%, the binder force generated by melting the organic resin during heat compression molding becomes too small, and sufficient bending stress cannot be obtained in the heat insulating sheet. On the other hand, if this content is more than 40 mass%, large voids are generated when decomposed by heating after application, so that the compressive strength is significantly reduced, and it becomes difficult to ensure a compressive strength of 0.55 MPa or more. Furthermore, if large voids are generated, the heat insulating property is also significantly reduced. In other words, the insulating sheet of an embodiment of the present invention has better insulating properties than still air because it contains countless small voids (microporous) that are small enough to inhibit the free movement of gas molecules, and therefore the insulating properties are significantly reduced when voids large enough to allow the free movement of gas molecules are formed.
[0023] The above components contained in the heat insulating sheet according to the embodiment of the present invention are appropriately adjusted in their blending ratio (content) so as to obtain the desired properties of the heat insulating sheet, taking into consideration the action and effect of each component. Specifically, the content of each of the above components constituting the heat insulating sheet according to the embodiment of the present invention is preferably 35 to 75 mass %, more preferably 40 to 60 mass %, for inorganic fine particles, preferably 10 to 30 mass %, for refractory fibers, preferably 8 to 20 mass %, for infrared scattering materials, and preferably 3 to 40 mass % for organic resins. It is preferable that these are contained in a total of 98 mass % or more, and inevitable impurities and molding aids may be included.
[0024] The heat insulating sheet according to the embodiment of the present invention has a bulk density of 200 to 500 kg / m 3 It is preferable that the thickness is 250 to 300 kg / m 3It is more preferable that the bulk density is 200 kg / m. This makes it possible to provide a heat insulating sheet that has both compressive strength and excellent heat insulating properties and is not easily damaged by compressive stress caused by thermal expansion. 3 If the bulk density is less than 500 kg / m, sufficient compressive strength cannot be obtained and handling properties may be insufficient. 3 If it exceeds this value, the strength is too high and good flexibility cannot be obtained.
[0025] Next, a method for manufacturing the heat insulating sheet according to the embodiment of the present invention will be described. In this method for manufacturing the heat insulating sheet, first, inorganic fine particles, fireproof fiber, infrared scattering material, and organic resin are blended and mixed in a mixer so as to have the above-mentioned content, and the resulting mixture is loaded into a compression molding machine and compressed to have the above-mentioned bulk density to form a molded body. Next, the resulting molded body is loaded into a heating press machine and heated to about 130 to 150 ° C. while applying pressure to perform heat compression molding. As a result, a part or whole of the fibrous or particulate organic resin is melted, and the inorganic fine particles, fireproof fiber, and infrared scattering material are thermally welded to each other via the organic resin, so that the deflection amount of the heat insulating sheet can be improved. EXAMPLES
[0026] Heat insulating sheets according to the present invention and comparative examples were prepared and each was evaluated in terms of bulk density, flexibility, radius of curvature, compressive strength, insulation, and heat resistance, which were determined by the following methods. That is, bulk density was determined by dividing mass by volume. Flexibility was determined in a three-point bending test using a strength tester, in which a 5 mm thick test piece was placed on two supports spaced apart by a distance (span) of 100 mm, and the maximum amount of deflection was measured when the center of the test piece was pressed down to break it, in a three-point bending test. The radius of curvature was determined as the radius of curvature at which breakage occurred when a 5 mm thick test piece was bent. Compressive strength was measured using the "compressive strength [N / mm 2 ] = (Maximum load (N) when the test piece is compressed by 10%) / area (mm 2) and was calculated from the maximum load when a specimen was compressed using a strength testing machine to produce a 10% strain. Thermal insulation was determined by measuring thermal conductivity at 600°C in accordance with the flat plate comparison method (JIS A1412-2 Appendix A). Heat resistance was determined as the maximum temperature at which the linear thermal shrinkage rate was 3% or less when the test specimen was heated for 24 hours.
[0027] [Example 1] The following mixtures were charged into a mixer and mixed: 65% by mass of siliceous particles (average particle size 0.2 μm) as inorganic particles, 10% by mass of glass fibers (E glass, average fiber diameter 13 μm) as fire-resistant fibers, 15% by mass of silicon carbide particles (average particle size 2 μm) as infrared scattering materials, and 10% by mass of polyethylene particles (average particle size 0.5 mm) as organic resin. The mixture thus obtained was charged into a mold and compression molded to form a flake-sheet-like molded body, which was then heated and compression molded at 150° C. to produce a heat insulating sheet with a thickness of 5 mm. The obtained heat insulating sheet had a bulk density of 300 kg / m 3 The deflection was 4.9 mm, the radius of curvature was 258 mm, the compressive strength was 0.78 MPa, the thermal conductivity was 0.03 W / (m·K), and the heat resistance temperature was 1000°C.
[0028] [Example 2] The bulk density was 200 kg / m3 in the same manner as in Example 1, except that the compression molding was performed so that the bulk density was 2 / 3 times that of Example 1. 3 The resulting insulation sheet had a deflection of 3.1 mm, a radius of curvature of 405 mm, a compressive strength of 0.64 MPa, a thermal conductivity of 0.03 W / (m K), and a heat resistance of 1000°C.
[0029] [Example 3] The bulk density was 500 kg / m3 in the same manner as in Example 1, except that the compression molding was carried out so that the bulk density was 5 / 3 times that of Example 1. 3 The resulting insulation sheet had a deflection of 3.0 mm, a radius of curvature of 418 mm, a compressive strength of 1.56 MPa, a thermal conductivity of 0.04 W / (m K), and a heat resistance of 1000°C.
[0030] [Example 4] A bulk density of 300 kg / m was obtained in the same manner as in Example 1, except that the blending ratio of the organic resin was 3 mass% and the blending ratio of the siliceous fine particles was 72 mass%. 3 The resulting insulation sheet had a deflection of 3.5 mm, a radius of curvature of 359 mm, a compressive strength of 0.85 MPa, a thermal conductivity of 0.03 W / (m K), and a heat resistance of 1000°C.
[0031] [Example 5] A bulk density of 300 kg / m was obtained in the same manner as in Example 1, except that the blending ratio of the organic resin was 40 mass% and the blending ratio of the siliceous fine particles was 35 mass%. 3 The resulting insulation sheet had a deflection of 5.3 mm, a radius of curvature of 238 mm, a compressive strength of 0.62 MPa, a thermal conductivity of 0.04 W / (m K), and a heat resistance of 1000°C.
[0032] [Example 6] A bulk density of 300 kg / m was obtained in the same manner as in Example 1, except that the particulate organic resin was replaced with a fibrous form of the same material (fiber diameter 1.7 dtex, fiber length 5 mm). 3 The resulting insulation sheet had a deflection of 9.1 mm, a radius of curvature of 142 mm, a compressive strength of 0.78 MPa, a thermal conductivity of 0.03 W / (m K), and a heat resistance of 1000°C.
[0033] [Example 7] A bulk density of 300 kg / m was obtained in the same manner as in Example 1, except that a polyethylene / polypropylene core-sheath structure fiber (fiber diameter 1.7 dtex, fiber length 5 mm) was used instead of the polyethylene particles in the organic resin. 3 The resulting insulation sheet had a deflection of 9.8 mm, a radius of curvature of 132 mm, a compressive strength of 0.78 MPa, a thermal conductivity of 0.03 W / (m K), and a heat resistance of 1000°C.
[0034] [Example 8] The bulk density was 300 kg / m in the same manner as in Example 6, except that alumina fine particles (average particle size: 0.2 μm) were used instead of silica fine particles as the inorganic fine particles. 3 The resulting insulation sheet had a deflection of 4.4 mm, a radius of curvature of 286 mm, a compressive strength of 0.77 MPa, a thermal conductivity of 0.03 W / (m K), and a heat resistance of 1200°C.
[0035] [Example 9] A bulk density of 400 kg / m was obtained in the same manner as in Example 1, except that magnesia fine particles (average particle size 0.2 μm) were used instead of silica fine particles as the inorganic fine particles and the bulk density was 4 / 3 times that of Example 1. 3 The resulting insulation sheet had a deflection of 4.8 mm, a radius of curvature of 260 mm, a compressive strength of 0.58 MPa, a thermal conductivity of 0.05 W / (m K), and a heat resistance of 1100°C.
[0036] [Example 10] A bulk density of 400 kg / m was obtained in the same manner as in Example 1, except that mullite fine particles (average particle size 0.2 μm) were used instead of silica fine particles as the inorganic fine particles and compression molding was performed so that the bulk density was 4 / 3 times that of Example 1. 3 The resulting insulation sheet had a deflection of 4.8 mm, a radius of curvature of 262 mm, a compressive strength of 0.65 MPa, a thermal conductivity of 0.05 W / (m K), and a heat resistance of 1100°C.
[0037] [Example 11] A bulk density of 400 kg / m was obtained in the same manner as in Example 1, except that zirconia-based fine particles (average particle size 0.2 μm) were used instead of silica-based fine particles as the inorganic fine particles and the bulk density was 4 / 3 times that of Example 1. 3 The resulting insulation sheet had a deflection of 5.0 mm, a radius of curvature of 242 mm, a compressive strength of 0.62 MPa, a thermal conductivity of 0.03 W / (m K), and a heat resistance of 1100°C.
[0038] [Example 12] A bulk density of 300 kg / m was obtained in the same manner as in Example 4, except that the silicon carbide content was zero, the blending ratio of organic particles was changed from 3% by mass to 8% by mass, and the blending ratio of fibrous organic resin (1.7 dtex, fiber length 5 mm) of the same material was changed to 10% by mass. 3 The resulting insulation sheet had a deflection of 5.0 mm, a radius of curvature of 230 mm, a compressive strength of 0.60 MPa, a thermal conductivity of 0.05 W / (m K), and a heat resistance of 1000°C.
[0039] [Example 13] A bulk density of 300 kg / m was obtained in the same manner as in Example 6, except that the glass fiber content was set to zero and the blending ratio of polyethylene particles (particle diameter 0.5 mm) as an organic resin was set to 10 mass % instead. 3 The resulting insulation sheet had a deflection of 3.0 mm, a radius of curvature of 400 mm, a compressive strength of 0.60 MPa, a thermal conductivity of 0.04 W / (m K), and a heat resistance of 1000°C.
[0040] [Example 14] A bulk density of 300 kg / m was obtained in the same manner as in Example 6, except that the blending ratio of AES (alkaline earth silicate) fiber (the content of non-fiber particles is 50 parts by mass per 100 parts by mass of refractory fiber, and non-fiber particles with an average particle size of 425 μm or more are 1 part by mass) was changed to 10 mass% instead of glass fiber. 3 A heat insulating sheet having a thickness of 5 mm was produced. The obtained heat insulating sheet had a deflection of 4.4 mm, a radius of curvature of 288 mm, a compressive strength of 0.77 MPa, a thermal conductivity of 0.05 W / (m K), and a heat resistance temperature of 1000°C. The compounding ratios, manufacturing methods, and physical properties of the heat insulating sheets of Examples 1 to 14 above are summarized in Table 1 below.
[0041] [Table 1]
[0042] [Comparative Example 1] Bulk density is 180kg / m 3The same procedure as in Example 1 was repeated, except that the molded product obtained by compression molding so as to have a bulk density of 180 kg / m was used as a heat insulating sheet without being heated and compressed. 3 The resulting insulation sheet had a deflection of 1.8 mm, a radius of curvature of 695 mm, a compressive strength of 0.58 MPa, a thermal conductivity of 0.03 W / (m K), and a heat resistance of 1000°C.
[0043] [Comparative Example 2] Bulk density 510kg / m 3 The same procedure as in Example 1 was repeated except that the powder was compression molded to have a bulk density of 510 kg / m 3 The resulting insulation sheet had a deflection of 2.1 mm, a radius of curvature of 596 mm, a compressive strength of 1.65 MPa, a thermal conductivity of 0.04 W / (m K), and a heat resistance of 1000°C.
[0044] [Comparative Example 3] A bulk density of 300 kg / m was obtained in the same manner as in Example 1, except that the blending ratio of the organic resin was 2 mass% and the blending ratio of the siliceous fine particles was 73 mass%. 3 The resulting insulation sheet had a deflection of 2.4 mm, a radius of curvature of 545 mm, a compressive strength of 0.87 MPa, a thermal conductivity of 0.03 W / (m K), and a heat resistance of 1000°C.
[0045] [Comparative Example 4] A bulk density of 300 kg / m was obtained in the same manner as in Example 1, except that the blending ratio of the organic resin was 41 mass% and the blending ratio of the siliceous fine particles was 34 mass%. 3 The resulting insulation sheet had a deflection of 5.5 mm, a radius of curvature of 230 mm, a compressive strength of 0.50 MPa, a thermal conductivity of 0.06 W / (m K), and a heat resistance of 1000°C.
[0046] [Comparative Example 5] In the case of AES (alkaline earth silicate) fiber, the content of non-fiber particles was 65 parts by mass per 100 parts by mass of the fire-resistant fiber, and non-fiber particles having an average particle size of 425 μm or more were 3 parts by mass of the fiber. 3 A heat insulating sheet with a thickness of 5 mm was produced. The obtained heat insulating sheet had a deflection of 3.5 mm, a radius of curvature of 355 mm, a compressive strength of 0.85 MPa, a thermal conductivity of 0.03 W / (m K), and a heat resistance temperature of 1000°C. The compounding ratios, manufacturing methods, and physical properties of the heat insulating sheets of Comparative Examples 1 to 5 are summarized in Table 2 below.
[0047] [Table 2] [Explanation of symbols]
[0048] 1, 11 Molten metal container 2. Conventional insulation materials 12. Heat insulating sheet according to an embodiment of the present invention
Claims
1. A heat insulating sheet comprising a molded body in which inorganic fine particles made of a metal oxide as a main material are mixed with an organic resin at a content in the range of 3 to 40 mass%, the organic resin being bonded to the inorganic fine particles by thermal fusion, the amount of deflection at break being 3.0 mm to 10 mm when a 5 mm thick piece is measured for bending strength with a span of 100 mm, the thermal conductivity at 600°C being 0.03 W / (m·K) to 0.05 W / (m·K), the compressive strength being 0.55 MPa to 1.56 MPa, and the bulk density being 200 to 500 kg / m3.
2. The heat insulating sheet according to claim 1, characterized in that the heat resistant temperature is 1200°C or less.
3. A method for manufacturing an insulating sheet, characterized in that an organic resin is mixed with inorganic fine particles consisting mainly of a metal oxide, the mixture is compression molded, and then the resulting molded body is heated and compression molded (except when curing is performed in a pressurized water vapor saturated atmosphere) to thermally fuse the organic resin to the inorganic fine particles.
Citation Information
Patent Citations
Heat-insulating material and its manufacturing method
JP2008194974A
Thermal insulation material
JP2011073959A
Heat insulating material and method for manufacturing the same
JP2012145217A
Powder, molded body, encapsulated body, and method for producing the powder
JP2013028501A
Composite heat insulating material superior in flexibility
JP2016205728A